Abundance and distribution of european badger – meles meles (Linnaeus, 1758) in the Sierra de Mariola Natural Park (C. Valenciana) - Antonio Belda; Roque Belenguer; Benito Zaragozí; Vicente Ferri (Boletín de la Asociación de Geógrafos Españoles, 2016)
The main objective of this research was to determine the distribution of the badger (Melesmeles) in the Sierra de Mariola Natural Park. A better knowledge of their distribution will assist with the definition of management measures in the Natural Park. In 2009, using camera traps, 29,941 images were collected with any animal contact. From these images, the 0.16% of the photographs are registered with the badger and their presence was detected in 6 of the 63 grids (4 Km2) of Sierra de Mariola (9,38%). This study has allowed us to integrate the information collected in the field with existing data bases. We conclude that the situation of badger in Sierra de Mariola is not of concern.